Pembelajaran Puisi Siswa Sekolah Dasar Kelas IV - Ichsan Muhammad; Nuryansyah Adijaya (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2020)
Primary school students are the first generation of literature, especially poetry. Understanding of poetry certainly needs to be conveyed with methods and teaching materials that are sufficient to facilitate current needs. The Indonesian government through the Ministry of Education and Culture has disseminated integrated textbooks (Buku Tematik), one of which contains poetry lessons. This study aims to determine the extent of coverage of poetry teaching materials in the thematic books of grade IV with the Cita-Citaku theme. This research was conducted using a qualitative content analysis method on thematic books of grade IV with the Cita-Citaku theme. The data were collected by categorizing the contents of the book material into a number of categories of learning stages. The findings data were then validated using triangulation techniques. The results of this study indicate that the thematic book of grade IV with the Cita-citaku theme contains the educational side of learning poetry in the form of language features (words, lines, stanzas and rhymes). Future research is expected to reveal the coverage of the material in the thematic books for grades V and VI.